Jurnalisme Warga di Indonesia, Prospek dan Tantangannya - Kurniawan, Moch. Nunung (UI Scholars Hub, 2007)
This paper examines the experience of Radio Elshinta in Jakarta with people-initiated journalism long before the descriptor “citizen journalism” emerged as a topic of research in academic level. Elshinta has 100,000 listeners, most with no formal training in journalism, contributing to its news broadcast since 2000. This study compares Elshinta’s experience with a popular online citizen media portal Ohmynews in South Korea and attempts to identify the catalysts of ‘citizen journalism’ in the two countries. The case study is complemented by interviews with journalists from Ohmynews and Elshinta. The study concludes that despite the low penetration of internet in Indonesia, the predominantly oral culture and low level of education, the main factors for Elshinta’s productive engagement with its listeners are (a) the predominantly oral culture in Indonesia; (b) low literacy, thus they rely on radio as the primary source of information and entertainment; and (c) the popularity of mobile phones for interpersonal communication. However, Indonesian television and printed media have been slow in catching up with people-initiated journalism because of: (a) fear over losing its reputation as credible media organizations, and thus commercial trust; and (b) conflict between unedited reports by untrained reporters with the professional code of ethics and Press Law. Other obstacles in broadering people-initiated journalism in Indonesian mainstream media are the slow uptake of amateur handy-cam images by TV stations, slow internet access, lack of writing skills, and lack of interactivity in existing online newssites.